Vida Saludable: ¿Que Son las Medicinas? Búsqueda por Palabras - Karla P. Shelnutt (EDIS)
FCS-8855-Span, a 1-page handout by Karla P. Shelnutt, is the Spanish language version of FCS-8855, Healthy Living: What Are Medicines? Word Search, a word search using words that relate to medicines. Published by the UF Department of Family Youth and Community Sciences, June 2008.